Sustainable entrepreneurship and knowledge management: Role of green information technology in building sustainable entrepreneurial ecosystems - Muhammad Sadiq; Thuy Dung Pham Thi; Chi Minh Nguyen; Hai-Dung Do (Journal of Innovation & Knowledge (JIK), 2025)
Using green management practices to build sustainable entrepreneurship is both effective and challenging for growing businesses. Meanwhile, knowledge management has proven to be a critical part of contemporary business practices. Thus, there is a growing demand for socially and environmentally aware behaviour as a part of existing strategies for dealing with the effects of such practices in the realm of sustainable entrepreneurial ecosystems. This study adopts a dimensional view of the knowledge-management model and its effect on sustainable entrepreneurship in Malaysia. We also include green information technology (GIT) acceptance in the model to examine its moderating effect on the proposed model. Partial least-squares structural equation modelling is used to explore the connections among variables. The results reveal that knowledge creation and transfer have a significant and positive relationship with sustainable entrepreneurship. However, the application and use of knowledge have insignificant effects on sustainable entrepreneurship. We also find that GIT acceptance significantly moderates the relationship between knowledge creation, knowledge transfer and storage, and sustainable entrepreneurship. By contrast, it insignificantly moderates the association between the application and use of knowledge and sustainable entrepreneurship. Our findings can help those involved in sustainable entrepreneurship development to more effectively utilise knowledge creation, GIT acceptance and adoption, and knowledge application and use.
Keywords: O10; D83; 650; Knowledge creation; Knowledge transfer and storage; Application and use of knowledge; Green information technology; Sustainable entrepreneurship